Pemikiran Islam Wasathiyah Azyumardi Azra sebagai Jalan Moderasi Beragama - Atun Homsatun; Jamhari Jamhari; Mefta Setiani; Nurhidayah Nurhidayah; Andika Putra (Jurnal Riset Agama, 2021)
This study aims to discuss how the concept of Islam wasathiyah Azyumardi Azra as a way of religious moderation in Indonesia. This study uses a qualitative approach with descriptive-analytical method. Regarding the data, this research is library research, so the data used are books that are directly related to this research. The results and discussion in this study seek to explore the concept of Islam wasathiyah Azyumardi Azra as a way of religious moderation in Indonesia. This study concludes that the Islamic thought of Wasathiyah Azyumardi Azra as a way of religious moderation is to actualize the values of moderation that already exist in the Qur'an, achieve peace and contribute to civilized and progressive civilization. This study recommends the Indonesian Ministry of Religion to apply wasathiyah values in Islam as a way of religious moderation.